Superior thermal and oxygen barrier properties of high-entropy ferroelastic rare earth tantalate (8RE1/8)TaO4 - Jun Wang; Yongpan Zeng; Xiaoyu Chong; Manyu Zhang; Qianqian Jin; Yanjun Sun; Xiangwei Tang; Peng Wu; Jing Feng (Journal of Advanced Ceramics)
Thermal/environmental barrier coatings (T/EBCs) are used to protect hot-section superalloys and/or ceramic matrix composite components from hot corrosion and oxidation; however, the majority of T/EBCs exhibit extremely high thermal and ionic conductivities. Here, we obtain a novel rare-earth tantalate with excellent oxygen and thermal insulation via a high-entropy strategy. The high-entropy component (8RE1/8)TaO4 (RE = rare earth), which is designed by large size disorder and mass disorder, has been reassembled into a stabilized monoclinic structure. (8RE1/8)TaO4 had 30.0%–31.1% and 59.2%–67.5% lower intrinsic thermal conductivity than single-RE RETaO4 and 8(Y2O3–ZrO2) 8YSZ at 1200 °C, respectively, and exhibited lower intrinsic thermal conductivity across the entire temperature range of 100–1200 °C. This is the result of strong scattering by the phonon–phonon, grain boundary, domain boundary, dislocation, and vacancy defects. The ionic conductivity of (8RE1/8)TaO4 is 3712–29,667 times lower than that of 8YSZ at 900 °C, benefiting from the strong Ta–O bonding strength, low concentration of mobile oxygen vacancies and severe lattice distortions that impede carrier transport. Moreover, (8RE1/8)TaO4 had superior high-temperature stability and excellent mechanical properties. Analysis of above results demonstrates that (8RE1/8)TaO4 is a promising candidate for T/EBCs.